A review on: liposomes - K, Subba Reddy; M, Durga Srinivasa Rao; P, Venkatesh (International Journal of Indigenous Herbs and Drugs, 2022)
Liposomes, spherical shaped vesicles consisting of one or more phospholipid bilayers, were first described in the mid60s. Today, they are a very useful reproduction, reagent, and tool in various scientific disciplines, including mathematics and theoretical physics, biophysics, chemistry, colloid science, biochemistry, and biology. Among several talented new drug delivery systems, liposomes characterize an advanced technology to deliver active molecules to the site of action. Research on liposome technology has progressed from conventional vesicles to ‘second-generation liposomes’, in which long-circulating liposomes are obtained by modulating the lipid composition, size, and charge of the vesicle. Liposomes with modified surfaces have also been developed using several molecules, such as glycolipids. They are of 0.05- 5.0 micrometer in diameter. Liposomes are used for the treatment of various diseases like tumors or cancer. In this review article provides a Liposomal Drug Delivery System and various aspects related to liposome that can be studied.